Identification of four TTN variants in three families with fetal akinesia deformation sequence - Lihong Fan; Haibo Li; Ying Xu; Yingzhi Huang; Yeqing Qian; Pengzhen Jin; Xueping Shen; Zhi Li; Mingsong Liu; Yufei Liang; Guosong Shen; Minyue Dong (BMC Medical Genomics, 2024)
Abstract Background TTN is a complex gene with large genomic size and highly repetitive structure. Pathogenic variants in TTN have been reported to cause a range of skeletal muscle and cardiac disorders. Homozygous or compound heterozygous mutations tend to cause a wide spectrum of phenotypes with congenital or childhood onset. The onset and severity of the features were considered to be correlated with the types and location of the TTN variants. Methods Whole-exome sequencing was performed on three unrelated families presenting with fetal akinesia deformation sequence (FADS), mainly characterized by reduced fetal movements and limb contractures. Sanger sequencing was performed to confirm the variants. RT-PCR analysis was performed. Results TTN c.38,876–2 A > C, a meta transcript-only variant, with a second pathogenic or likely pathogenic variant in trans, was observed in five affected fetuses from the three families. Sanger sequencing showed that all the fetal variants were inherited from the parents. RT-PCR analysis showed two kinds of abnormal splicing, including intron 199 extension and skipping of 8 bases. Conclusions Here we report on three unrelated families presenting with FADS caused by four TTN variants. In addition, our study demonstrates that pathogenic meta transcript-only TTN variant can lead to defects which is recognizable prenatally in a recessive manner.